2016
DOI: 10.1128/aem.01994-16
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Glucose and Starch on Lactate Production by Newly Isolated Streptococcus bovis S1 from Saanen Goats

Abstract: When ruminants are fed high-concentrate diets, Streptococcus bovis proliferates rapidly and produces lactate, potentially causing rumen acidosis. Understanding the regulatory mechanisms of the metabolism of this species might help in developing dietary strategies to alleviate rumen acidosis. S. bovis strain S1 was newly isolated from the ruminal fluid of Saanen dairy goats and then used to examine the effects of glucose and starch on bacterial metabolism and gene regulation of the organic acid-producing pathwa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 40 publications
(40 reference statements)
2
20
0
Order By: Relevance
“…Maybe the LDH is all used to neutralize LACT and further investigation is needed to explain this phenomenon. AMY activity of fermenting microorganisms is an important factor in the fermentation of starch to lactate [ 56 ]. Previous studies have demonstrated that the concentration of AMY was related to dry matter intake and nutrient composition, and more starch intake may enhance the AMY concentration in the small intestine [ 57 , 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…Maybe the LDH is all used to neutralize LACT and further investigation is needed to explain this phenomenon. AMY activity of fermenting microorganisms is an important factor in the fermentation of starch to lactate [ 56 ]. Previous studies have demonstrated that the concentration of AMY was related to dry matter intake and nutrient composition, and more starch intake may enhance the AMY concentration in the small intestine [ 57 , 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…The increasing glucose promotes the production of pyruvate in the rumen. On the other hand, pyruvate can be converted to lactate by lactate dehydrogenase (LDH) (Chen et al 2016 ) or converted to acetyl coenzyme-A and formate by pyruvate formate-lyase (PFL) (Asanuma and Hino 2000 ), then acetyl-CoA is converted either to acetate or ethanol. Under anaerobic condition, PFL is a central enzyme to degrade pyruvate to acetyl-CoA and the enzyme comprises the cofactors S-adenosylmethionine and thiamine diphosphate (TPP) (Knappe et al 1969 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to overall proliferation, alterations in microbial ecology and dysbiosis occur, and losses in microbial richness and diversity in response to acidotic diets are observed in both rumen fluid and cecum digesta/feces [ 33 , 34 , 35 ]. As a result, not only fermentation rates, but also patterns change, enhancing lactate synthesis and buildup and further contributing to the pH decline [ 36 , 37 ].…”
Section: Intestinal Health and Inflammationmentioning
confidence: 99%